Acute microplastic exposure raises stress response and suppresses detoxification and immune capacities in the scleractinian coral Pocillopora damicornis. (December 2018) - Tang, Jia; Ni, Xingzhen; Zhou, Zhi; Wang, Lingui; Lin, Senjie
Abstract: Microplastics are widespread emerging contaminants that have been found globally in the marine and freshwater ecosystem, but there is limited knowledge regarding its impact on coral reef ecosystem and underpinning mechanism. In the present study, using Pocillopora damicornis as a model, we investigated cytological, physiological, and molecular responses of a scleractinian coral to acute microplastic exposure. No significant changes were observed in the density of symbiotic zooxanthellae during the entire period of microplastic exposure, while its chlorophyll content increased significantly at 12 h of microplastic exposure. We observed significant increases in the activities of antioxidant enzymes such as superoxide dismutase and catalase, significant decrease in the detoxifying enzyme glutathione S-transferase and the immune enzyme alkaline phosphatase, but no change in the other immune enzyme phenoloxidase during the whole experiment period. Transcriptomic analysis revealed 134 significantly up-regulated coral genes at 12 h after the exposure, enriched in 11 GO terms mostly related to stress response, zymogen granule, and JNK signal pathway. Meanwhile, 215 coral genes were significantly down-regulated at 12 h after exposure, enriched in 25 GO terms involved in sterol transport and EGF-ERK1/2 signal pathway. In contrast, only 12 zooxanthella genes exhibited significant up-regulation and 95 genes down-regulation at 12 h after the microplastic exposure; genes regulating synthesis and export of glucose and amino acids were not impacted. These results suggest that acute exposure of microplastics can activate the stress response of the scleractinian coral P. damicornis, and repress its detoxification and immune system through the JNK and ERK signal pathways. These demonstrate that microplastic exposure can compromise the anti-stress capacity and immune system of the scleractinian coral P. damicornis, despite the minimal impact on the abundance and major photosynthate translocation transporters of the symbiont in the short term. Graphical abstract: Image 1 Highlights: Zooxanthella chlorophyll content increased significantly after microplastic exposure. The activities of antioxidant enzymes were induced by microplastic exposure. Detoxifying and immune enzyme activities were repressed by microplastic exposure. GO terms related to JNK/ERK pathway were enriched for differentially expressed genes. Abstract : Microplastic exposure can activate the stress response of P. damicornis and repress its detoxification and immune system through the JNK and ERK signal pathways.